Coaxial electrical circuits for interference-free measurements - Awan, Shakil, 1971- (Institution of Engineering and Technology, 2011)
Annotation This title offers guidance and best practice in electrical measurements applicable to any required accuracy level.
Keywords: Electric measurements.; elektronické knihy; electronic books